2019
DOI: 10.21608/zjar.2019.65067
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Planting Density, Nitrogen and Potassium Fertilizer Levels on Yield and Quality of Sugar Beet

Abstract: Two field experiments were carried out at the experimental farm (Ghazala Village), Faculty of Agriculture, Zagazig University, Sharkia Governorate, during 2016/2017 and 2017/2018 seasons to study the influence of three planting densities, (28000, 35000 and 46666 plants/fad.) three levels of N fertilizer (80,100 and 120 kg/fad.) and two levels of potassium fertilizer (24 and 48 kg k 2 O/fad.) on yield and its attributes as well as quality of sugar beet grown in clay soil. Results of combined analysis illustrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Sugar beet production increase owing to favorable accessible soil moisture in sugar beet root zone by spray irrigation system may be attributed to reducing water constraint, particularly in freshly planted sugar beets. These findings are consistent with those of (Abd El-Kader, 2005;Ahmad et al, 2010Ahmad et al, , 2015Al-jbawi et al, 2015;El-Geddawy et al, 2008;El-Hawary et al, 2019;Hanafy et al, 2019;Nafei and Osman, 2010;Saini and Brar, 2018;Varga et al, 2021) who reported that using suitable planting method and optimum plant density increased growth, yield and quality of field crops. Bed planting not only lowers operational costs, but also improves water distribution and efficiency .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Sugar beet production increase owing to favorable accessible soil moisture in sugar beet root zone by spray irrigation system may be attributed to reducing water constraint, particularly in freshly planted sugar beets. These findings are consistent with those of (Abd El-Kader, 2005;Ahmad et al, 2010Ahmad et al, , 2015Al-jbawi et al, 2015;El-Geddawy et al, 2008;El-Hawary et al, 2019;Hanafy et al, 2019;Nafei and Osman, 2010;Saini and Brar, 2018;Varga et al, 2021) who reported that using suitable planting method and optimum plant density increased growth, yield and quality of field crops. Bed planting not only lowers operational costs, but also improves water distribution and efficiency .…”
Section: Resultssupporting
confidence: 87%
“…Planting sugar beet plants at the highest plant density of 56000 plants/fed (15 cm between hills) yielded the highest values of sucrose percent, to yield /fed, root yield /feddan, and sugar yield/fed, while the lowest plant density 33600 plants/fed yielded the longest root, widest root, and heaviest root when compared to other plant densities (El-Hawary et al, 2019). The highest plant density (46666 plants/fed) produced higher sucrose, extractable sugar percentages, sugar and recoverable sugar yields/fed., than at low or medium densities (Hanafy et al, 2019).In the other study, planting two rows on the bed with a Plant density of 123000 plants/ha recorded maximum production efficiency, monetary efficiency and sugar productivity (9.65 and 8.62 t/ha), which was on par with planting two rows on both sides of the ridge with a plant density of 123000 plants/ha and significantly higher than rest of the treatment (Saini et al, 2020). In relation to plant density, higher plant densities had on average the highest root yield, sucrose content, and white sugar yield (Varga et al, 2021).…”
mentioning
confidence: 93%
“…Using the Micro-computer Statistical (MSTAT-C) software package (Mstat 6.1.4, Michigan State University, USA), all data were statistically analyzed in accordance with the technique of analysis of variance (ANOVA) for the strip plot design. The least significant difference (LSD) method was used to test the differences between treatment means at the 5% level of probability (Gomez and Gomez 1984;Steel and Torrie, 1997). For a better understanding of the link between the researched qualities across experimental conditions, Pearson's correlation analysis was employed.…”
Section: Statistical Analysis Methodsmentioning
confidence: 99%
“…In this concern, Enan et al (2016), foliar application of potassium compound at a rate of 2 L ha -1 significantly improved sugar beetroot yield, root fresh weight, sucrose content, and root yield. Leilah et al (2005), Hanafy et al (2019, Leilah and Kan (2021) reported the sucrose content of sugar beetroot declined with incremental levels of N, root length, root fresh weight, plant canopy, and root yield increased. Mekdad and Rady (2016) found spraying of a micronutrient mixture containing iron-Fe, zinc-Zn, and manganese-Mn boosted sugar beet crop yield and its characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In sugar beet, K is also involved in biosynthesis and transfer of sucrose to storage roots [ 8 ]. Hanafy et al [ 9 ] found that the application of K significantly improved root yield, length, diameter and fresh root weight of sugar beet. Additionally, many studies have reported that K and N enhance the biosynthesis of organic metabolites which increase the yield and quality of sugar beet [ 10 ].…”
Section: Introductionmentioning
confidence: 99%